The impact of childhood maltreatment on aggression, criminal risk factors, and treatment trajectories in forensic psychiatric patients - Koolschijn, Marijtje; Janković, Marija; Bogaerts, Stefan (Frontiers in Psychiatry, 2023)
Children's development into healthy well-functioning adults can be negatively affected by adversity. Adverse childhood experiences (ACEs) have been shown to lead to a variety of poor life outcomes, ranging from mental health problems (e.g., anxiety or suicidality) through problematic health behaviors to serious physical diseases and even early death. ACEs can also make people more prone to aggressive behavior, criminality, and recidivism. In this study, we investigated the association between ACEs, specifically childhood maltreatment (CM), and forensically relevant factors; aggression, criminal risk factors, and treatment trajectories, as little is known about these associations in forensic psychiatric patients. The study includes data derived from two studies in The Netherlands, of which the first study enrolled 128 patients residing in a Forensic Psychiatric Center (FPC) and the second study included 468 patients who were released unconditionally from FPCs between 2009 and 2013. We expected that more CM would be correlated with higher levels of aggression, higher clinical risk factor scores, and less decrease in clinical risk factor scores over time. To investigate this, we applied correlational analyses and linear growth curve modeling on risk assessment scores and self-report as well as staff report questionnaires on CM and aggression. Consistent with our first hypothesis, patients with higher CM scores also had higher aggression and risk assessment scores. The effect sizes were small to medium (0.12 to 0.34). Unexpectedly, CM did not influence the course of these treatment trajectories, however, we found that patients with histories of CM had a significantly longer length of stay in a forensic facility than patients without CM (respectively 10.8 years and 9.3 years on average). This study underlines the importance of carefully examining the history of ACEs and CM in forensic psychiatric patients and considering this in forensic risk assessment and risk guided treatment. More research is needed to draw conclusions about whether and how histories of ACEs should be considered and targeted during treatment trajectories.